Inovasi Pengembangan Usaha Virgin Coconut Oil (VCO) di Desa Sulang, Klungkung - Sumartana, I Made; Widnyani, Ida Ayu Putu Sri; Dewi, Cokorde Istri Dian Laksmi; Indramanik, Ida Bagus Gede; Utama, I Gusti Bagus Rai (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This study aims to determine the prospects of VCO business development in Sulang Village, Dawan District, Klungkung Regency. Research methods: Respondents and samples in this study were four traditional coconut oil craftsmen. Based on the results of the pretest and posttest, there were positive results, where craftsmen were very enthusiastic about developing VCO production. This is supported by the availability of abundant raw materials, availability of low-wage labor. Results and discussion: Although there are still shortcomings/weaknesses and challenges, the opportunities are quite large for the success of VCO production, when compared to producing traditional coconut oil. In order for the VCO production business to continue, partnerships with stakeholders, such as: Department of Trade and Industry, Department of Health, Pharmacies, Salons and SPAs, Gift Shops. And to introduce the production of VCO can utilize social media as a means to promote its production. Implication: The development of traditional oil-making businesses with fermentation techniques that produce Virgin Coconut Oil (VCO) in Sulang Village, Dawan District, Klungkung Regency has bright prospects in the future, for this reason, researchers suggest that related parties, especially those who take care of MSMEs, can provide assistance and guidance so that existing small businesses can develop even more advanced.